2019
DOI: 10.1002/csr.1824
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethical leadership and corporate social responsibility on firm performance: A systematic review

Abstract: Academic and corporate interest in ethical leadership, corporate social responsibility (CSR), and firm performance has attracted a lot of attention in recent years. In fact, many research papers and journal special issues have been focused on these three domains. In this context, this paper conducts a systematic review on the concepts of ethical leadership and CSR and their impact on firm performance. 114 papers published over a period of 58 years (1958–2016) were selected and analyzed according to descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(177 citation statements)
references
References 174 publications
6
126
2
7
Order By: Relevance
“…Consistent with hypothesized relations, our research supported the direct impact of consumer perception of CSR on brand passion. This finding is in line with past publications, which revealed a considerable influence of CSR initiatives on marketing outcomes such as a firm's sales performance (Saha et al, 2020), brand loyalty (Ghauri et al, 2015), and actual buying behavior (Eshra & Beshir, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with hypothesized relations, our research supported the direct impact of consumer perception of CSR on brand passion. This finding is in line with past publications, which revealed a considerable influence of CSR initiatives on marketing outcomes such as a firm's sales performance (Saha et al, 2020), brand loyalty (Ghauri et al, 2015), and actual buying behavior (Eshra & Beshir, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Ghauri et al (2015) reported that CSR associations influence consumers' product evaluation. Likewise, Holt et al (2004); Saha et al (2020), in a marketing domain, reported that CSR explains brand preferences in the way that consumers perceive that global brands have a responsibility to deal with societal issues. Another study by Vlachos and Vrechopoulos (2012) noted that customer perception of CSR positively influences their brand love.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different types of reviews that can be conducted (Snyder, 2019), we can recall narrative reviews (Perego et al, 2016), systematic reviews (Centobelli, Cerchione, Chiaroni, Del Vecchio, & Urbinati, 2020;Cillo, Messeni Petruzzelli, Ardito, & Del Giudice, 2019;Saha, Shashi, Cerchione, Singh, & Dahiya, 2019;Widyawati, 2019;Tranfield et al, 2003), structured literature reviews (Massaro, Dumay, & Guthrie, 2016) We opted for a systematic review because it allows research on a particular question to be comprehensively located and synthesized, using organized, transparent, and replicable procedures at each step in the process (Littell, 2008) and because it is characterized, with respect to the traditional narrative review, by the rigor of the search process (Kitchenham & Charters, 2007). In detail, we follow the four steps proposed by Fink (2010), enriched using the structure proposed by Tranfield et al (2003), consistently with Stechemesser and Guenther (2012).…”
Section: Methodsmentioning
confidence: 99%
“…Though there is no widely accepted definition of CER [7,8,23,24,25,26,27,28,29,30], for the sake of convenience, we support that CER is one of three facets of CSR, and focuses on pollution prevention and cleaner production. Furthermore, we regard the following terms as equivalent to CER: CSR in the environment, environmental CSR, environmental corporate responsibility.…”
Section: Literature Reviewmentioning
confidence: 65%